Is housing a public health issue? A survey of directors of public health. Issue 6769 (19th January 1991) - Roderick, P; Victor, C; Connelly, J
Abstract : OBJECTIVE--To determine the views of directors of public health on the importance of housing for public health and their departments' and health authorities' participation in housing issues. DESIGN--Postal self administered questionnaire survey. SETTING--All district health authorities in England and health boards in Wales, Scotland, and Northern Ireland. SUBJECTS--All 221 district directors of public health in England and chief administrative medical officers in Wales, Scotland, and Northern Ireland. MAIN OUTCOME MEASURE--Response to questionnaire consisting of fixed and open ended questions on housing issues. RESULTS--The response rate was 89% (196/221). Housing was perceived as a major health problem by 33% (65/196) of directors. Positive responses were most likely from inner city districts. In 47% (93/196) of departments there was a formal time commitment to housing issues with a median time of one session/week (range one per month to 10 per week). The main function was allocation of medical priority for public sector rehousing. Overall, 73% (144/196) reported some participation in this process. Reported participation in joint care planning and links with non-statutory housing organisations were uncommon. 53% (104/196) of directors had included housing issues in their annual health report. In 16% (32/196) of districts specific services for the homeless had been set up. CONCLUSIONS--Although concern about the impact of current housing policy on public health was shown by a substantial number of directors, the main activity was still allocation of medical priority despite a background of increasing housing need and homelessness. The underlying need is for greater advocacy to produce a healthy housing policy for all, and the annual public health report could be used to promote this objective.